The Well-Made (Feminist) Play: Malena Sándor’s Challenge to Theatrical Conventions - Farnsworth, May Summer (Latin American Theatre Review, 2003)
This article analyzes the comic innovations made by Argentine feminist playwright Malena Sándor in the 1930s and 1940s. While the comedies studied here, Yo me divorcio, papá (1937), Una mujer libre (1938), Tu vida y la mía (1945), and Ella y Satán (1948), are conventional and realistic in structure, they are notably subversive in their message. Sándor’s spectators are drawn into the action and encouraged to consider feminism through her unique renovated-realistic formula. Her adaptations of realistic theatre include role-play, and a correction of the limitations traditionally imposed on women through patriarchal uses of theatrical space and dramatic discourse. (MSF)